The Correlation Between Marketing Mix And Patient Loyalty At Sentra Medika Hospital North Minahasa Outpatient Unit - Ringkuangan, Rivaldy; Kolibu, Febi K; Mandagi, Chreisye K.F (Journal of Literacy and Education, 2025)
The healthcare industry in Indonesia has experienced rapid development over the past few decades. As of 2023, there are 2,636 general hospitals (RSU) and 519 specialty hospitals (RSK) across Indonesia, reflecting the high demand for access to healthcare services. An appropriate hospital marketing strategy, such as the implementation of the marketing mix, is crucial for sustaining services and enhancing hospital competitiveness. Based on the background described, the research problem is formulated as follows: Is there a relationship between the marketing mix and outpatient loyalty at Sentra Medika Hospital North Minahasa? The research aims to examine the relationship between the marketing mix and patient loyalty in the outpatient unit at Sentra Medika Hospital North Minahasa. This research employed a quantitative approach with a cross-sectional study design, focusing on a sample of non-BPJS outpatient unit patients visiting Sentra Medika Hospital Minahasa Utara. The findings revealed a significant positive relationship between the marketing mix and patient loyalty at Sentra Medika Hospital North Minahasa. The conclusion drawn from this study is that there is a significant relationship between the marketing mix and patient loyalty in the outpatient unit of Sentra Medika Hospital Minahasa Utara. As a recommendation, the hospital should conduct further research by incorporating additional variables that may influence patient loyalty and continue to develop marketing strategies in line with evolving trends over time.